Guerre à la Carte: Cyber, Information, Cognitive Warfare and the Metaverse - Marsili, M. (Applied Cybersecurity & Internet Governance, 2023)
Hybrid warfare is among the most trending topics. Hybrid threats arise in digital, cybernetic, and virtual environments and materialize in the real world. Although vague, hybrid activities include cyberwarfare, information warfare, and the emerging and evolving concept of cognitive warfare which appears from their intersection. These fuzzwords gained popular attention in the context of the Russo-Ukrainian conflict and now are among the hot topics. While there is a lot of attention, there is also a lot of confusion about what exactly these locutions mean and what the implications are in branding them as “warfare”. Indeed, all these concepts are fluid, nebulous, and lack an undisputed legal definition. This article aims to clarify the meaning and to shed light on the characteristics of such terms – differences, similarities and overlaps – in the context of hybrid warfare and show the faulty reasoning upon which misunderstandings are based. The paper ends-up with a glimpse into the future, closing with a reflection on multi-domain operations facilitated by a fully integrated human-computer interaction in the metaverse, where physical reality is merged and interact with digital virtuality.